Small-spored Alternaria spp. (section Alternaria) are common pathogens on wild tomato species - Schmey, T.; Small, C.; Einspanier, S.; Hoyoz, L.M.; Ali, T.; Gamboa, S.; Mamani, B.; Sepulveda, G.C.; Thines, M.; Stam, R. (Wiley, 2023)
The wild relatives of modern tomato crops are native to South America. These plants occur in habitats as different as the Andes and the Atacama Desert and are, to some degree, all susceptible to fungal pathogens of the genus Alternaria. Alternaria is a large genus. On tomatoes, several species cause early blight, leaf spots and other diseases. We collected Alternaria-like infection lesions from the leaves of eight wild tomato species from Chile and Peru. Using molecular barcoding markers, we characterized the pathogens. The infection lesions were caused predominantly by small-spored species of Alternaria of the section Alternaria, like A. alternata, but also by Stemphylium spp., Alternaria spp. from the section Ulocladioides and other related species. Morphological observations and an infection assay confirmed this. Comparative genetic diversity analyses show a larger diversity in this wild system than in studies of cultivated Solanum species. As A. alternata has been reported to be an increasing problem in cultivated tomatoes, investigating the evolutionary potential of this pathogen is not only interesting to scientists studying wild plant pathosystems. It could also inform crop protection and breeding programs to be aware of potential epidemics caused by species still confined to South America.